Relative Extensions of Modules and Homology Groups - Lixin Mao; Haiyan Zhu (Український математичний журнал, 2015)
We introduce the concepts of relative (co)extensions of modules and explore the relationship between the relative (co)extensions of modules and relative (co)homology groups. Some applications are given. Введено поняття відносних (спів)розширень модулів та вивчено взаємозв'язок між відносними (спів)розширеннями модулів та відносними (ко)гомологічними групами.